Strategi Pemasaran Shopee Express dan JNT Express Melalui Analisis SWOT dan QSPM - Syakila, Mutiara; Mekanza, Muhammad Alif; Hannes, Mutiara; Daratulaila, Intan; Fikri, Khusnul (Universitas Batanghari Jambi, 2024)
Current economic progress has made many companies increasingly compete to meet consumer needs. This has led to the emergence of the goods delivery service sector within the company. With the goods delivery service, people can easily shop even though the seller and buyer do not meet in person. This research uses a purposive technique, namely focusing on informants in the case unit to be studied. Respondents in this research numbered 30 people per expedition. The data collection techniques used were interviews and questionnaires. The data analysis technique used is SWOT and QSPM analysis with the help of Ms. software. Excel and SPSS. The results of the research are: (1) Based on the results of the IFAS and EFAS matrices, the total weight x IFAS rating is 3.94 and the total weight of the EFAS rating is 2.98. SWOT for strategies that can be carried out according to the results of the IE matrix, namely grow and build strategy in cell IV. (2) From the results of the QSPM matrix calculation, 3 alternative strategies were obtained that were the most attractive and prioritized for Shoope Express. First, increasing the reach of shops to have Shopee Express services by providing regulations that require all shops on Shopee e-commerce to have Shopee Express services. Second, collaborating with other e-commerce to increase users of Shopee Express services. When, adding branches to remote corners of the country. (3) Based on the results of the IFAS and EFAS matrices, the total weight x IFAS rating is 3.18 and the total weight of the EFAS rating is 3.15. SWOT for strategies that can be carried out according to the results of the IE matrix, namely grow and build strategy in cell I. (4) From the results of the QSPM matrix calculation, 3 alternative strategies are obtained which are the most interesting and prioritized to be carried out. First, one day delivery for outside the city because currently there is only one day delivery within the city. Second, there is a need to maintain JNT branding by providing training. Third, increase discount programs to maintain customer loyalty.